FALL PREVENTION KNOWLEDGE FOR THE ELDERLY AMONG NURSES AT FRIENSHIP HOSPITAL AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2021)
Falls in older persons occur commonly. Falls can cause death, reduced quality of life, and increased costs of treatment. Nurses play an important role in preventing falls for the older patients. A cross-sectional descriptive study was conducted on 189 nurses to describe the nurses’ knowledge at Friendship hospital on fall prevention and some related factors. 63.5% of nurses achieved general fall prevention knowledge; 47.6% of them had good knowledge about risk factors for falls; 55% of them had good knowledge of fall risk assessment; 84.1% of them had good knowledge of fall prevention measures for older patients. The fall prevention knowledge showed a significant difference statistically in the fields of updating fall prevention knowledge, wanting to learn about fall prevention and fall prevention education.
Keywords: Fall, elderly, nurse, knowledge.